Multiple interest rate analysis : theory and applications - Osborne, Michael; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book is an analysis of all possible interest rates. Dual expressions are used to solve long-standing puzzles, eliminate anomalies and draw conclusions about best practice and sound policy advice in areas of economics and finance. Topics include retail and corporate finance, capital budgeting and investment appraisal, bond risk management. A model demonstrating some of the ideas in the book is available in the Wolfram Demonstrations Project: demonstrations.wolfram.com/AModelIllustratingMultipleInterestRateAnalysisMIRA/. A free'computable document' containing the model is available for download from the same site.
Keywords: Finance; Accounting; Bookkeeping; Corporations -- Finance; Risk management; Financial engineering; International economics